(untitled) (Gestão & Regionalidade, 2018)
In response to demands for research focusing on the vulnerability of people with disabilities who are consumers, this research has set the objective of understanding how is the consumer with Down syndrome vulnerability revealed in their interactions with the market environment of Rio de Janeiro city. In the empirical part of the study, semi-structured in-depth interviews have been conducted with eighteen Down subjects and with their relatives, in a total of 44 informants. Data collection has been anchored in narratives of life stories, photographs description, and application of projective techniques. Treated by content analysis, the data generated four categories: the first is related to urban mobility, the second to the socio-technical environment of the market, the third to problems involving money and credit, and finally the fourth to the consumer with Down syndrome invisibility. Keywords: Consumer vulnerability; exclusion; Down syndrome.